Emerging challengers in knowledge-based industries? The case of Indian pharmaceutical multinationals - Gert Bruche (Columbia University, Vale Columbia Center on Sustainable International Investment (VCC), 2011)
The growth of outward foreign direct investment (FDI) from developing countries and of a new generation of "emerging multinational enterprises" (EMNEs) has stimulated a flurry of publications. EMNEs have been portrayed as on their way to adulthood, latecomers that leapfrog into advanced positions, emerging giants, and challengers of conventional multinational enterprises (MNEs) from advanced economies.
Keywords: 330